2021
DOI: 10.1016/j.celrep.2020.108678
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic compensation activates pro-survival mTORC1 signaling upon 3-phosphoglycerate dehydrogenase inhibition in osteosarcoma

Abstract: Highlights d Upregulated PHGDH in osteosarcoma correlates with poor survival d Inhibiting PHGDH attenuates osteosarcoma proliferation without causing cell death d TCA cycle blockade and accumulation of metabolites results in mTORC1 activation d PHGDH inhibition combined with non-rapalog mTORC1 inhibition is synergistic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…SAMTOR and GATOR1 interactions are dependent on KICSTOR (see below). When SAMTOR is bound to SAM, it dissociates from GATOR1-KICSTOR, thus inhibiting GATOR1 and promoting mTORC1 activation [101]. On the other hand, methionine starvation promotes interaction between SAMTOR and the GATOR1-KICKSTOR complex, but weakened the interaction between GATOR1 and GATOR2, thus leading to mTORC1 suppression [100].…”
Section: Gator1 Interaction With Sam Sensor Samtormentioning
confidence: 99%
“…SAMTOR and GATOR1 interactions are dependent on KICSTOR (see below). When SAMTOR is bound to SAM, it dissociates from GATOR1-KICSTOR, thus inhibiting GATOR1 and promoting mTORC1 activation [101]. On the other hand, methionine starvation promotes interaction between SAMTOR and the GATOR1-KICKSTOR complex, but weakened the interaction between GATOR1 and GATOR2, thus leading to mTORC1 suppression [100].…”
Section: Gator1 Interaction With Sam Sensor Samtormentioning
confidence: 99%
“…Osteosarcoma is the prevalent malignant bone cancer principally befalling throughout adolescence and childhood (Du et al, 2021;Gioti et al, 2021). Osteosarcoma emphasizes the profoundly malignant phenotypes, and 75% of osteosarcoma cells migrate nearby tissues (Li et al, 2021;Rathore et al, 2021). Although the overall 5-years survival incidence of osteosarcoma patients has improved by applying surgery and chemotherapy over the past 30 years, prognosis continues unsatisfactory due to drug resistance and metastasis (Wen et al, 2020;Tornin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A previously published study illustrated the importance of metabolism in OS as metastatic OS cells were found to be highly metabolically active, and therefore targeting metabolism in OS can be a potential novel therapy [6]. Furthermore, it was shown that both the inhibition of mTOR-a key regulator of metabolism, and the inhibition of 3-phosphoglycerate dehydrogenase (PHGDH)-the rate-limiting enzyme of serine biosynthesis, attenuated cell proliferation in OS cells and can therefore serve as a novel therapeutic target [7][8][9]. The NAD+ synthesis pathway is a metabolic pathway often upregulated in tumors as cancer cells need to maintain a high level of NAD+ required for cell survival processes [10,11].…”
Section: Introductionmentioning
confidence: 99%